2016
DOI: 10.1161/jaha.115.003003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PTCSC3 as a Novel Locus for Large‐Vessel Ischemic Stroke: A Genome‐Wide Association Study

Abstract: Background--Ischemic stroke is a major cause of death and disability in the world. A major ischemic stroke subtype, large-vessel ischemic stroke (large artery atherosclerosis; LAA), has been shown to have some genetic components in individuals of European ancestry. However, it is not clear whether the genetic predisposition to LAA stroke varies among ethnicities. We sought to identify genetic factors that contribute to LAA stroke in 2 independent samples of Han Chinese individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Papillary thyroid carcinoma susceptibility candidate 3 is a newly identified lncRNA, which is predisposed expressed in papillary thyroid cancer . A study reported that PTCSC3, a 1152‐bp lncRNA, attenuated thyroid cancer by repressing cell proliferation and invasion .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Papillary thyroid carcinoma susceptibility candidate 3 is a newly identified lncRNA, which is predisposed expressed in papillary thyroid cancer . A study reported that PTCSC3, a 1152‐bp lncRNA, attenuated thyroid cancer by repressing cell proliferation and invasion .…”
Section: Discussionmentioning
confidence: 99%
“…Papillary thyroid carcinoma susceptibility candidate 3 (PTCSC3) is a lncRNA gene located 3.2 kb downstream of SNPP rs944289 at chromosome 14q.13.3 . It has been reported that lncRNA PTCSC3 is associated with papillary thyroid cancer (PTC) susceptibility .…”
Section: Introductionmentioning
confidence: 99%
“…These included variants at the 9p21 locus (25,26), ABO and HDAC9 (27,28). Several novel loci, which were associated with ischemic stroke or large-artery stroke, have been identified recently, including MMP12 (29), PTCSC3 (30), and ALDH2 (31). All of these studies shed light on the different pathogenic pathways underpinning stroke subtypes.…”
Section: Genetics Of Sporadic Ischemic Strokementioning
confidence: 99%
“…Evidence obtained from family, twin and animal model studies has revealed a genetic predisposition to the risk of ischemic stroke. [3][4][5][6] To date, genome-wide association studies have identified a series of genetic risk factors associated with ischemic stroke, [7][8][9][10][11] although some of them still need to be confirmed.…”
Section: Introductionmentioning
confidence: 99%